Hydrothermally engineered enhanced hydrate formation for potential CO2 capture applications - Mohd Hafiz Abu Hassan; Farooq Sher; Saba Sehar; Tahir Rasheed; Ayesha Zafar; Jasmina Sulejmanovi´c; Usman Ali; Tazien Rashid (Elsevier LTD., 2024)
Indexed by WOS/SCOPUS/ERA